From Molecules to Mind: The Critical Role of Chitosan, Collagen, Alginate, and Other Biopolymers in Neuroprotection and Neurodegeneration - Weronika Kruczkowska; Julia Gałęziewska; Katarzyna Helena Grabowska; Piotr Gromek; Karolina Czajkowska; Maciej Rybicki; Mateusz Kciuk; Karol Kamil Kłosiński (Molecules)
Neurodegenerative disorders present significant therapeutic challenges, particularly due to the complex nature of drug delivery to the central nervous system. This review investigates the applications of various biopolymers in neuroprotection and their potential role in treating neurodegeneration. We present a critical analysis of natural and synthetic biopolymers, focusing primarily on chitosan, fish collagen/gelatin, and alginate as key therapeutic agents. The review examines the fundamental mechanisms of brain development and neurodegeneration, establishing a framework for understanding how these biopolymers interact with neural tissues. By analyzing recent experimental studies, we evaluate the effectiveness of different biopolymer-based delivery systems in crossing the blood–brain barrier and their subsequent neuroprotective effects. Additionally, promising materials, including lignin, poly lactic-co-glycolic acid, and glucose-modified bovine serum albumin/procyanidin complexes, are briefly explored to provide a comprehensive overview of current developments in the field. Our analysis reveals that biopolymer-based approaches offer unique advantages in both neuroprotection and drug delivery, potentially opening new avenues for treating neurodegenerative conditions. This review synthesizes current knowledge and identifies promising directions for future research in biopolymer-based therapeutic strategies.